COE and car prices : the Singapore experience. - Goh, Daniel Koon Yu. (2011)
In Singapore, consumers are required to purchase a Certificate of Entitlement (COE), before they can own a car. COE is a first-of-its-kind vehicle ownership tax, comprising five categories: Category A-E. This paper considers only three categories: Category A for passenger cars that are 1600cc and below (including taxis); B for those above 1600cc; and E, for the purchase of any vehicles from Category A-D.